2016
DOI: 10.6000/1929-6002.2016.05.02.2
|View full text |Cite
|
Sign up to set email alerts
|

Trend Topic Analysis for Wind Energy Researches: A Data Mining Approach Using Text Mining

Abstract: This study reviews and analyses the recent research and development and trends in the applications of wind energy and it also discusses and summarizes the topic. We show the usage and the influence of text mining on the different aspects of wind energy systems especially for hot topics and trends of wind energy area. Text mining provides the state of the art in this area that will be a good guidance for future research work. The main results achieved from the study have shown that the text mining technique are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Kim et al ( 6 ) performed a study into bioinformatics that aimed to generate a system to provide reference materials to let NLP techniques work in bio-text mining. Also, they used text mining techniques to identify trend topics and study clusters in the area of wind energy ( 7 ). Shi et al ( 8 ) used a methodology perspective to identify risk factors in safety management systems.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al ( 6 ) performed a study into bioinformatics that aimed to generate a system to provide reference materials to let NLP techniques work in bio-text mining. Also, they used text mining techniques to identify trend topics and study clusters in the area of wind energy ( 7 ). Shi et al ( 8 ) used a methodology perspective to identify risk factors in safety management systems.…”
Section: Literaturementioning
confidence: 99%
“…Country Rankings on Number of Publications until the End of the Year 2018 into bioinformatics that aimed to generate a system to provide reference materials to let NLP techniques work in bio-text mining. Also, they used text mining techniques to identify trend topics and study clusters in the area of wind energy(7).Shi et al …”
mentioning
confidence: 99%
“…Ayrıca, yatırımcılar küresel ve yerel pazardaki yerlerini koruyabilmek için mevcut rüzgâr çiftliklerinde maliyetleri düşürecek kontrol ve izleme araçları geliştirmek için büyük çaba göstermektedirler [8]. Eroğlu ve Seçkiner'in [9] hazırladıkları bir çalışmaya göre, rüzgâr enerjisi ile ilgili yapılan 7000'den fazla makale incelenmiş ve özellikle son dönemlerde maksimum güç üretimine, en etkin parametrelerle beraber yönetimsel amaçlarla ve bu doğrultuda dinamik ve akıllı kontrol yöntemlerine odaklanıldığı belirtilmiştir. Özetle, mevcut literatüre göre akademik çalışmalar "Bir rüzgâr santrali hangi etkin parametrelerde en yüksek performansta çalışır?"…”
Section: şEkilunclassified
“…Moreover, they emphasized that new methods and technologies should be developed in airline operations to minimize the damage by considering environmental factors. As for examples from the field of energy, text mining research in the literature for the trend of optimization studies in wind energy [10] and the analysis of wind turbine accident news can be examined as examples [11]. In line with the research of the authors, almost no study was found using the text mining method related to forest fires; the exception was a study based on the analysis of tweets posted after the forest fire [12].…”
Section: Introductionmentioning
confidence: 99%
“…Text contents are analyzed with a suitable text mining software (Statistica's text mining tool was used in this study. The use of Statistica's text mining tool along with the user interfaces is given in step-by-step reference [10]);…”
mentioning
confidence: 99%